Black Soldier Fly Larvae (BSFL) Bioconversion for Circular Economy: A Study in Polaman Village - Sumardiono, Siswo; Amalia, Rizka; Dhiya’ulhaq, Syaikha Butsaina; Ilmi, Nurika Nazilatul; Ariyanto, Hermawan Dwi (ASEAN Journal of Community Engagement, 2024)
Conventional organic waste management methods often lead to environmental degradation and underutilization of valuable resources. In rural areas, such as Polaman Village, limited awareness and inefficient disposal systems exacerbate these issues, thus necessitating innovative and sustainable solutions. This study explores black soldier fly larvae (BSFL) bioconversion as a community-based solution for organic waste management, addresses environmental challenges, and promotes economic empowerment by converting waste into valuable by-products. The study employed a mixed-methods approach, beginning with baseline assessments of waste generation and existing management practices to identify community needs. Educational workshops and hands-on training sessions introduced BSFL bioconversion techniques to local stakeholders. Focus group discussions (FGDs) were conducted to facilitate dialog and collaboration between Polaman residents, the Polaman Resik Sejahtera Waste Bank, and Universitas Diponegoro. Continuous mentoring and pilot trials were conducted to ensure proper adoption and to demonstrate the feasibility of the proposed system. The results reveal that BSFL bioconversion significantly reduces organic waste while producing valuable by-products such as compost and larvae. These findings demonstrate the potential of BSFL bioconversion to align with circular economy principles, contributing to environmental sustainability and economic resilience. The project serves as a scalable model for addressing organic waste challenges in rural communities while advancing the green economy agenda.